Familiness in Intra-organizational Relations and the Personnel Policy in Family Businesses - Joanna LERCHE; Anna LEMAŃSKA-MAJDZIK (Communications of International Proceedings, 2020)
Properly developed relationships are one of the elements that determine development opportunities of enterprises. Familiness resulting from the specificity, characteristics and values held in family businesses affects the shape of intra-organizational relationality as well as building working atmosphere. The management of intra-organizational relations is an intangible resource of the organization of particular strategic value. Therefore, the attention should be drawn to the significance of relational capital and its impact on the ability to manage human resources as well as organizational culture in family businesses. The objective of the article is to examine the impact of the family nature of the enterprise on building intra-organizational relations. During the analysis the attention has been paid to selected aspects of the personnel policy, including organizational culture of the enterprise, working atmosphere, stabilization and professional development as well as motivation of employees hired. The research conducted on Polish workers of family businesses in the second half of 2020 allowed for responding to the formulated research question. The research results confirmed that the basis for building positive intra-organizational relations is working atmosphere. The concern of employers for positive relationships with employees often brings a range of benefits, and the values associated with the family as well as characteristics such as trust, loyalty, tradition, enhance a sense of bond and identity of hired employees.
Keywords: Intra-Organizational Relations; Personnel Policy; Management of Family Businesses; Family Company